Current Research Trends in Wire Electrical Discharge Machining (WEDM): A Review - Aidil, A.R.M.; Minhat, M.; Hussein, N.I. S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Wire Electrical Discharge Machine (WEDM), a non-traditional machining process, is becoming more important in providing a non-contact machining process. It is suitable for machining geometrically complex and hard advanced material which is impossible to machine using the conventional machine. This paper reviewed the experimental results on performance evaluation of machining parameters which affected machining performance which would reflect the machining factors and responses. In addition, the methods in analyzing, modelling, development and tool steel in WEDM were also discussed. Some recommendations and future WEDM research were proposed.